THE NEW CHOICE OF LAW RULES IN TORTS: THE AFTERMATH OF TOLOFSON V. JENSEN; LUCAS V. GAGNON - Swan, John (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 1999)
The recent cases of Tolofson v. Jensen and Lucas v. Gagnon have again brought the problem of the Conflict of Laws to the forefront of Canadian law. The structure of Canadian conflict of laws analysis dictates that when there is an issue of foreign law, it must be characterized as either a substantive or procedural question. In the former case, further characterization into category of law is required, e.g. whether it is a contracts or a torts question. In the latter case, the lex fori, or the law of the forum applies. In Tolofson/Gagnon, the Supreme Court decided not only that questions of limitation period are questions of substance rather than procedure, but also that the choice of law rule in torts is that of lex loci delicti, i.e., the law of the place of the wrong determines the rights and obligations of the parties. The article addresses the choice of law aspects of the Tolofson/Gagnon decision and the form of the rule, the ability to justify its application and the general structure of conflict analysis. The court's reasons for the choice of law rule were simplicity and certainty, and respecting the limits on provincial powers. It is argued that the adoption of the rule was unexpected, and it was followed neither in Canada, nor in the U. S.. The Ontario case of Hanlan v. Sernesky demonstrates that the lex loci delecti rule will not provide certainty because in cases where lex loci leads to injustice, the judge has discretion to apply the lex fori. The author maintains that while the facts and reasons of Hanlan cannot be distinguished from Tolosfon/Gagnon, the two cases came to opposite results.Given the uncertainty created by the structure of conflict analysis, "escape devices" have been adopted by English, French, Canadian and American courts to avoid the application of the law "selected" by the choice of law rule. The first device discussed was to adjust the characterization of the question, so that for example, it would be examined as a contracts or family law question rather than a torts one. The characterization of the question is particularly important because every question must be answered by the same choice. Another device is the use of the doctrine of renvoi which includes in the conflict analysis, the choice of law rule of the foreign law. Tolofson/Gagnon is hard to reconcile with other SCC cases such as Morguard, Moran and Amchem, as the former denies the development that the SCC can oversee litigation with a foreign element and ensure that Canadian values are represented. The author clearly indicates that he is unhappy with this situation and that he hopes for a quick change in the Canadian case law.